Differential modulation of lung aquaporins among other pathophysiological markers in acute (Cl2 gas) and chronic (carbon nanoparticles, cigarette smoke) respiratory toxicity mouse models - Bhattacharya, Sukanta S.; Yadav, Brijesh; Yadav, Ekta; Hus, Ariel; Yadav, Niket; Kaur, Perminder; Rosen, Lauren; Jandarov, Roman; Yadav, Jagjit S. (Frontiers in Physiology, 2022)
Inhaled toxic chemicals and particulates are known to disrupt lung homeostasis causing pulmonary toxicity and tissue injury. However, biomarkers of such exposures and their underlying mechanisms are poorly understood, especially for emerging toxicants such as engineered nanoparticles and chemical threat agents such as chlorine gas (Cl2). Aquaporins (AQPs), commonly referred to as water channels, are known to play roles in lung homeostasis and pathophysiology. However, little is known on their regulation in toxicant-induced lung injuries. Here, we compared four lung toxicity models namely, acute chemical exposure (Cl2)-, chronic particulate exposure (carbon nanotubes/CNT)-, chronic chemical exposure (cigarette smoke extract/CSE)-, and a chronic co-exposure (CNT + CSE)- model, for modulation of lung aquaporins (AQPs 1, 3, 4, and 5) in relation to other pathophysiological endpoints. These included markers of compromised state of lung mucosal lining (mucin 5b and surfactant protein A) and lung-blood barrier (protein content in bronchoalveolar lavage fluid/BAL, cell tight junction proteins occludin and zona-occludens). The results showed toxicity model-specific regulation of AQPs measured in terms of mRNA abundance. A differential upregulation was observed for AQP1 in acute Cl2 exposure model (14.71-fold; p=0.002) and AQP3 in chronic CNT exposure model (3.83-fold; p=0.044). In contrast, AQP4 was downregulated in chronic CSE model whereas AQP5 showed no significant change in any of the models. SP-A and MUC5B expression showed a decreasing pattern across all toxicity models except the acute Cl2 toxicity model which showed a highly significant upregulation of MUC5B (25.95-fold; p=0.003). This was consistent with other significant pathophysiological changes observed in this acute model, particularly a compromised lung epithelial-endothelial barrier indicated by significantly increased protein infiltration and expression of tight junction proteins, and more severe histopathological (structural and immunological) changes. To our knowledge, this is the first report on lung AQPs as molecular targets of the study toxicants. The differentially regulated AQPs, AQP1 in acute Cl2 exposure versus AQP3 in chronic nanoparticle (CNT) exposure, in conjunction with the corresponding differentially impacted pathophysiological endpoints (particularly MUC5B) could potentially serve as predictive markers of toxicant type-specific pulmonary injury and as candidates for future investigation for clinical intervention.